Evaluation of Production and Economic Feasibility of Using the Recommended Nutrient Requirement for Lactating Cows - T, Ahmed Nabaweia; Elabid, K.E.; Elseed, A.M. Fadel; Elhag, A. (Pakistan Journal of Nutrition, 2010)
An experiment was carried out to evaluate production and economic feasibility of using the recommended nutrient requirements for lactating cows in small scale dairy farms in Khartoum state. The study consisted of two parts; a survey of 90 dairy farms in Khartoum State and an experiment carried out on 16 lactating dairy cows in the Judiciary farm. These cows were divided into two groups: A and B (8 cows in each group). Group A was distributed in eight pens and given balanced ration, whereas group B was fed as practiced in the farm. The experiment lasted for seven months extending from January to July 2007. The survey results revealed that the balanced ration costs were only 23, 38 and 55% of unbalanced ration at 10, 15 and 20 lbs level of milk production respectively. The results of the experiment revealed that the use of balanced ration increased the cow milk production by 27% compared with the unbalanced ration. The four months milk yield of cows fed balanced and unbalanced ration were significantly different (P<0.05). The mean cost of four months milk production for cows fed balanced ration was significantly (P<0.05) lower than these fed unbalanced ration, being 435 and 578 SDG, respectively. The mean cost of production per pound of milk for cows fed balanced ration was significantly (P<0.05) lower than the cows fed unbalanced ration; it was 0.107 and 0.206 SDG, respectively. The balanced ration has a greater trend coefficient of 32.36 compared with 18.56 for the unbalanced ration. In conclusion, the balanced ration increased the level of cow milk production and decreased the cost milk production compared to unbalanced ration.